1965
DOI: 10.1515/bchm2.1965.340.1-2.200
|View full text |Cite
|
Sign up to set email alerts
|

Reaktionen von Pyrrolonverbindungen IX. Mitteilung zur Stokvis-Reaktion

Abstract: Das5.5 / -Dioxo-2.5-dihydro-5'J3'-dipyrroinethan-(2.2 / ) bzw. das 5-Hydroxy-5'-oxo-5'#-dipyrromethan-(2.2')** wurden von uns als mögliche stabile Formen des 5.5'-Dihydroxy-l#-dipyrromethens-(2.2') beschrieben 3 . Wollte man zur Synthese dieses Verbindungstyps vom leicht zugänglichen Pyrrolon-(2) ausgehen, so wäre es zweckmäßig, dieses zuerst in der Enolform zu fixieren. So haben beispielsweise Plieninger et al. 4 2-Alkoxy-5-formyl-pyrrol mit 2-Alkoxy-pyrrol zum Dipyrromethen-diäther umgesetzt. Eine geringe Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1968
1968
1979
1979

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…(A9), (10 ' 12 ' 13) or if it is substituted only in the 5-position by an alkyl group, e.g. (9) The same compound, however, has also been formulated as (A12) (16) and a more recent reinterpretation of the IR and NMR spectroscopic data indicates the correct structure to be that of the 5-hydroxymethylene-A 3 -pyrrolin-2-one (A13). ( It was originally thought that an electron-withdrawing group in the 5-position stabilized the 2-hydroxy form, e.g.…”
Section: O» Ex Exmentioning
confidence: 99%
See 2 more Smart Citations
“…(A9), (10 ' 12 ' 13) or if it is substituted only in the 5-position by an alkyl group, e.g. (9) The same compound, however, has also been formulated as (A12) (16) and a more recent reinterpretation of the IR and NMR spectroscopic data indicates the correct structure to be that of the 5-hydroxymethylene-A 3 -pyrrolin-2-one (A13). ( It was originally thought that an electron-withdrawing group in the 5-position stabilized the 2-hydroxy form, e.g.…”
Section: O» Ex Exmentioning
confidence: 99%
“…Prolonged reaction of 3-ethyl-4-methyl-A 4 -pyrrolin-2-one with benzoyl chloride has been reported, however, to produce the 5-benzoyl-2-benzoyloxy compound (16) and, similarly, it has been found that prolonged Schotten-Baumann benzoylation of 3-amino-2,4-diphenylpyrrole will give the mesophenyldipyrrylmethene via the 3-benzamido-5-benzoylpyrrole (see Chapter 4, Section F). (56,6o,77,83,ioo,m) c f benzoylation of pyrroles (see Chapter 4, Section F).…”
Section: C41mentioning
confidence: 99%
See 1 more Smart Citation